Facing criticism: an analysis of (land-based) corporate responses to the large-scale land acquisition countermovement. Issue 5 (29th July 2019) - Salverda, Tijo
ABSTRACT: This contribution analyses how corporations involved in large-scale land acquisition respond to a countermovement of critics such as non-governmental organisations, local communities, peasant movements, scholars and journalists. Though the countermovement rightly receives much attention, its impact on corporations/investors is less discussed. International guidelines and corporate pledges to ban 'land grabbing' in their operations, however, may be signs that critics have some influence. Yet by no means has this proven to be sufficient. Starting from a study of a European agribusiness operating in Zambia, this paper aims to provide a nuanced understanding of the extent to which corporations are susceptible to a countermovement.